A risk management model for securing virtual healthcare communities. (20th December 2011) - Chryssanthou, Anargyros; Varlamis, Iraklis; Latsiou, Charikleia
Virtual healthcare communities aim to bring together healthcare professionals and patients, improve the quality of healthcare services and assist healthcare professionals and researchers in their everyday activities. In a secure and reliable environment, patients share their medical data with doctors, expect confidentiality and demand reliable medical consultation. Apart from a concrete policy framework, several ethical, legal and technical issues must be considered in order to build a trustful community. This research emphasises on security issues, which can arise inside a virtual healthcare community and relate to the communication and storage of data. It capitalises on a standardised risk management methodology and a prototype architecture for healthcare community portals and justifies a security model that allows the identification, estimation and evaluation of potential security risks for the community. A hypothetical virtual healthcare community is employed in order to portray security risks and the solutions that the security model provides.